RELATIONSHIP BETWEEN STRATEGIC LEADERSHIP AND THE MANAGEMENT OF SCHOOLS ACCORDING TO FOUR BRAHMA VIHARA PRIRCIPLES UNDER NAKHON SI THAMMARATCITY MUNICIPALITY - Choysatit, Yaowarat; Aunjanam, Santi; Saengamporn, Sranya (Journal of Srilanchang Review, 2022)
The objectives of this article are as follows: 1) to study the level of strategic leadership of school administrators in schools affiliated with Nakhon Si Thammarat Municipality, 2) to study the level of school administration according to Brahma Vihara 4 principles of schools affiliated with Nakhon Si Thammarat Municipality, 3) To study the relationship between the strategic leadership of school administrators and the administration of educational institutions according to Brahma Vihara 4 principles of schools affiliated with Nakhon Si Thammarat Municipality, The population includes teachers and school personnel affiliated with Nakhon Si Thammarat Municipality. Of the 9 schools, 573 students were employed by convenient sampling method. Krejcic and Morgan sample sizes were determined using the Krejcic and Morgan table, a sample of 286 people. The research tool is a questionnaire with a confidence value of 0.95 Frequency distributions, percentages, averages, standard deviations, and Pearson correlation coefficients are obtained. The results showed that Strategic leadership of school administrators in schools affiliated with Nakhon Si Thammarat Municipality Overall, was at a high level. When considered on a side-by-side basis, sorted by descending average. It was found that the strategy formulation had the highest average, followed by the direction of the organization. The strategy control and evaluation section has the least average. The administration of educational institutions according to brahma vihara 4 of the schools affiliated with Nakhon Si Thammarat Municipality. Found Mutita It has the highest average, followed by the leggy side, the benevolent side The results of the analysis of the relationship between the strategic leadership of school administrators and the administration of educational institutions according to brahma vihara 4 principles of schools affiliated with Nakhon Si Thammarat Municipality. Overall, there is a very high level of correlation. Statistically significant at .01 levels are consistent with assumptions